"Jesus got crucified, why should we expect any different?"; UK Christian clergies' experiences of coping with role demands and seeking support*. Issue 4 (21st April 2022) - Edwards, Laura; Sabin-Farrell, Rachel; Bretherton, Roger; Gresswell, David M.; Tickle, Anna
ABSTRACT: Clergy have an emotionally taxing role and are suggested to experience high rates of distress. Prior research suggests clergy utilise religious coping skills and may underutilise support. This study aimed to explore clergy experiences of role-demands, coping, and support, to supplement previous findings, and guide intervention. Nine clergy members participated in semi-structured interviews; data was analysed using inductive-deductive Thematic Analysis. Three major themes emerged from the data; 'the sacrifice you make', 'help along the way', and 'change that's needed'. Clergy-members' most prevalent and salient reported coping strategy revolved around a stable relationship with God. Clergy discussed barriers to support within, and outside of, the church. Clergies' experiences of challenging demands and distress support previous findings. Clergy preference for religious coping suggest future research, or intervention, should account for spirituality. Finally, clergy-members' varied experiences of support suggest practical/cultural changes within the church could reduce barriers.